Porovnání nákladů u režimů XELOX a FOLFOX-4 v léčbě kolorektálního karcinomu - Büchler, T; Nohejlová Medková, A; Kupec, M; Bláha, M; Pavlík, T; Dušek, L; Abrahámová, J (Klinicka onkologie, 2012)
BACKGROUND: The aim of our study was to compare healthcare-related costs of treatment with XELOX and FOLFOX4 chemotherapeutic regimens in patients with colorectal cancer. We have evaluated costs claimed to the health insurance by the hospital administering these cancer therapies. This study is a pilot project utilising the new I-COP database developed by the Institute of Biostatistics and Analyses of the Masaryk University in Brno, Czech Republic. PATIENTS AND METHODS: First, we estimated the costs based on current prices of procedures, medication, and materials from public sources. Using the I-COP database, we then carried out a matched-pair comparison of 26 patients treated with FOLFOX4 or XELOX for colorectal cancer. We evaluated a period of three months of therapy (i.e. 6 cycles of FOLFOX4 or 4 cycles of XELOX). Statistical analysis was done using the Wilcoxon matched pairs test. RESULTS: The estimated cost for three months of therapy was 148,288 Czech crowns (CZK) for FOLFOX4 (including CZK 101,064 for chemotherapy drugs) and CZK 123,756 for XELOX. The overall costs claimed to the insurance companies were CZK 160,158 and CZK 151,176 for FOLFOX4 and XELOX, respectively (p = 0.221). The XELOX regimen had significantly higher costs for chemotherapy drugs (CZK 131,705 versus 114,531, p = 0.023) whereas other costs were lower than those for FOLFOX4. CONCLUSIONS: FOLFOX4 and XELOX regimens can be considered as equivalent in terms of costs claimed by the hospital administering cancer treatment.
Keywords: senioři; Capecitabine; Oxaloacetates; senioři nad 80 let; kolorektální nádory; Česká republika; fluoruracil; Fluorouracil; Deoxycytidine; capecitabinum; Middle Aged; Colorectal Neoplasms; mužské pohlaví; Organoplatinum Compounds; oxalacetáty; Adult; Czech Republic; náklady a analýza nákladů; Aged, 80 and over; ženské pohlaví; Humans; deoxycytidin; organoplatinové sloučeniny; Leucovorin; leukovorin; lidé středního věku; Antineoplastic Combined Chemotherapy Protocols; protokoly protinádorové kombinované chemoterapie; dospělí; Female; Aged; Costs and Cost Analysis; lidé; Male